The Influence of Brand Image, Price, and Product Quality on the Purchase Decision of Kopiko 78˚c at PT. XYZ - Widi Lusiana; Sudarijati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The intense competition among companies engaged in the packaged coffee beverage sector encourages companies to have reliable strategies in order to be able to increase business growth and win marketshare. This study aims to analyze the effect of brand image, price and product quality on purchasing decisions for packaged beverage products Kopiko 78°C at PT. XYZ. The subject of this research is the consumer, PT. XYZ; as many as 100 consumers were used as samples. This research is descriptive and verifiable. The data collection procedure in this study used a literature study and field studies (questionnaires and interviews). The instrument testing method uses validity and reliability tests. Methods of data analysis using multiple linear regression analysis, correlation coefficient analysis, analysis of the coefficient of determination, and significance tests simultaneously and partially. The results showed that the brand image, price and product quality were in a good category. Partially and simultaneously, brand image, price and product quality have a positive and significant effect on purchasing decisions.